Lessons for IELTS : Advanced writing. (Tp.HCM : Nxb. Tổng hợp Tp.HCM : Nhân Trí Việt, 2013)
Introduction; Task 1 Marking Criteria; Line graphs; ...
New oriental education & technology group IELTS research institute.
Keywords: IELTS; English language -- Writing -- Study and teaching